Database security and study of data encryption methods in cloud storage - Shcherbinina, Ye.; Martseniuk, B.; Filonenko, A. M. (Полтавський національний технічний університет ім. Юрія Кондратюка, 2020)
Purpose of the article is discusses the importance of database encryption and makes an in depth review of various encryption techniques. Security of Data is the most important task in today’s world. Governments, companies and other organizations have lost a lot of money and many others have closed down due to the activities of dubious hackers and attackers. Over the years various encryption schemes have been developed in order to protect the database from various attacks by the intruders. As data is the life wire of every organization, there is the need to remotely and securely store the data generated daily by these organizations in order to enable them recover quickly in the event of attach and hack. Cloud storage is needed here for the remote data storage. For many establishments, data security is one of their major concern when sending their files into the cloud. They worry about their files being seen or even compromised by malicious and dubious people because that’s what happened in the past. Data encryption techniques are required to protect the integrity of the stored data. In the past, many businesses felt comfortable allowing the cloud providers to manage all their data, believing that security risks could be managed through contracts, controls and audits. Over time it has become apparent, however, that cloud providers cannot honor such commitments when responding to government requests for information. This paper discuses, the importance of database encryption and makes an in depth review of various encryption techniques.

Мета статті – об проаналізувати питання щодо важливості шифрування бази даних та зробити глибокий огляд різних методів шифрування. Безпека даних - найважливіше завдання в сучасному світі. Влада, компанії та інші організації втратили багато грошей, а багато інших закрилися, через діяльність хакерів і зловмисників. За минулі роки були розроблені різні схеми шифрування для захисту бази даних від атак зловмисників. Оскільки дані - це життєвий канал кожної організації, існує потреба в безпечному зберіганні даних, щодня генерованих цими організаціями. Хмарне сховище необхідно для віддаленого зберігання даних. Для багатьох підприємств безпека даних є однією з основних проблем при відправці файлів в хмару. Вони турбуються про те, що їх файли будуть переглянуті або навіть скомпрометовані. Для захисту цілісності даних, що зберігаються, необхідні методи шифрування даних. У минулому багато компаній відчували себе комфортно, дозволяючи постачальникам хмарних послуг управляти всіма своїми даними, вважаючи, що ризиками безпеки можна керувати за допомогою контрактів, засобів контролю і аудиту. Однак з часом стало очевидно, що постачальники хмарних послуг не можуть виконувати такі зобов'язання. У цьому документі обговорюється важливість шифрування бази даних і дається детальний огляд різних методів шифрування.
Безпека бази даних і вивчення методів шифрування даних в хмарному сховищі
Keywords: encryption; cryptography; hashing; database; cloud storage; cipher text; шифрування; криптографія; хешування; база даних; хмарне сховище; зашифрований текст